Proof of concept of an automated CoCoRaHS rain gauge - Lin, Jieqi, author; Johnson, Gearold R., advisor; Troxell, Wade O., committee member; Siller, Thomas J., committee member (Colorado State University. Libraries, 2016)
CoCoRaHS is the Community Collaborative Rain, Hail and Snow Network, collecting daily precipitation reports from volunteers’ reading of a low-cost plastic 4-inch diameter rain gauge. Nolan Doesken, the Colorado State Climatologist following the disastrous Fort Collins flood of July 1997, created the network. Today there are more than 20,000 rain gauges in service. There are three limitations in the present CoCoRaHS rain gauge. The first limitation is limited temporal granularity, i.e., data measurements are only available once each 24-hours, in the best cases. The second limitation is not being able to capture data during an extreme event as it is occurring. The third limitation is because this is a volunteer activity other activities may interfere with the ability to collect daily data. The question is can the CoCoRaHS rain gauge be modified to eliminate these three restrictions while keeping the design as similar to the current system as possible. The design is to turn the present rain gauge into a weight-based automated rain gauge. An in-lab tested prototype was built requiring only that the rain gauge bracket needed modification. The result is a modified bracket holding a load-cell, microcontroller and Wi-Fi communications subsystems. A number of experiments were designed and conducted to prove the feasibility of the rain gauge. The conclusion is that a low-cost, high-accuracy weight-based automated CoCoRaHS rain gauge is achievable.